Penerapan Manajemen Nyeri Dengan Terapi Relaksasi Otot Progresif Penderita Hipertensi - Erman, Imelda; Shobur, Sherli; Utami, Mega; Febriani, Indra; Athiutama, Ari (JKM : Jurnal Keperawatan Merdeka, 2024)
Background: Hypertension is one of the non-communicable diseases (PTM) which is currently increasing both prevalence and incidence, especially in the elderly group. Hypertension is a systolic blood pressure of more than 140 mmHg and a diastolic pressure of more than 90 mmHg. Methods: This case study uses a descriptive design with a nursing process approach. This research was conducted on March 7, 2022 to March 11, 2022. The number of samples used was 2 people with 4 consecutive days of action. The research was conducted in the Working Area of the Merdeka Health Center in Palembang. Results: The results showed that after the action of progressive muscle relaxation therapy for 4 days, there was a change in the pain scale from pain scale 4 to 2 in client 1 and client 2 from pain scale 5 to pain scale 2. Conclusion: The results of the study indicate that there are changes in the headache scale of hypertensive patients before and after progressive muscle relaxation therapy for 4 days with a time of approximately 15 minutes.